The Effect of Compound Exercises Using Added Relative Weights On Some Physical Abilities In Young Soccer Players - Katee, Muhammed; Jadem, Muayad (Journal of Physical Education, 2019)
The research aim at designing training using added relative weights as well as identifying the effect of these trainings on some physical abilities. The researchers used the experimental method on (10) sport clubs with (25) young soccer players for each club making a total of (250) player.  The subjects included (25) Al Shorta club players divided into (10) controlling group, (10) experimental group and (5) pilot study subjects. The researchers designed physical exercises using relative weights for target muscles in soccer. The training program consisted of three training sessions per week for (6) weeks. The researchers concluded that exercises using added relative weights have a positive effect on some physical abilities. Finally the researchers recommended using compound exercises in young soccer players’ physical preparation.